Genius : a mosaic of one hundred exemplary creative minds - Bloom, Harold (New York : Warner Books, 2002)
"What is genius? It is the trait, says Harold Bloom, of standing both of and above its age, the ancient principle that recognizes and hallows the God within us, and the gift of breathing life into what is best in every living person." "From the Bible to Socrates, through the transcendent achievements of Shakespeare and Dante, down through the ages to Hemingway, Faulkner, and Ralph Ellison, the author explores the numerous parallels between his chosen geniuses and the surprising ways they have influenced one another over the centuries. Genius also offers revealing excerpts from their works that continue to surprise, enchant, and move readers time after time. Suffused with his infectious and inexhaustible enthusiasm, Bloom's insightful analyses of the poetry of Milton, Shelley, and Whitman; the drama of Ibsen and Tennessee Williams; and the narratives of Melville and Tolstoy, among many others, illuminate and expand our common understanding and love of these great works of art.".
"Illustrated with portraits of many of the featured writers, this book is the culmination of Harold Bloom's half-century of teaching and writing about literature - and a grand yet intimate tour of Western literary and spiritual culture in one magnificent volume. Enriching as it informs, Genius is a book to savor and to treasure."--BOOK JACKET.
Includes bibliographical references.
Keywords: Genius; Gifted persons